PROLACTIN AND HOSTILITY IN HOSPITALISED PATIENT AND HEALTHY WOMAN: A SYSTEMATIC REVIEW - Laurenso Lomi, Eldwin (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
These maternal adaptations are the result of dynamic changes in key hormones during pregnancy and lactation, which act on neural circuits in the brain. Lactogenic hormones (for example, prolactin and its pregnancy-specific homolog, placental lactogen) are significant regulators of these processes, with receptors located in key brain areas controlling emotional behaviors and maternal reactions. Prolactin (PRL) receptors are most typically found in the hypothalamus, where females have the highest amounts of binding. It has been proven beyond doubt that the hypothalamus has a role in the control of aggressive behavior in humans. This notion is particularly plausible for women. However, some research suggests that there is no link between PRL levels and levels of rage or aggression. This could be due, at least in part, to the fact that the participants in the several research were of different sorts, as discussed in the following section. PRL is enhanced not only after giving birth, but also as a result of other occurrences. Increased PRL levels have been associated to a variety of factors, including but not limited to pregnancy, primary hyperthyroidism, medications, pituitary tumor, stress, anxiety, and pain. According to studies, hospitalized patients had greater prolactin levels than healthy people. Stress, depression, anxiety, and other mood disorders are all linked to high prolactin levels.